Time-Resolved Photoluminescence Microscopy for the Analysis of Semiconductor-Based Paint Layers - Comelli, Daniela; Artesani, Alessia; Nevin, Austin; Mosca, Sara; Gonzalez, Victor; Eveno, Myriam; Valentini, Gianluca (Materials, 2017)
In conservation, science semiconductors occur as the constituent matter of the so-called semiconductor pigments, produced following the Industrial Revolution and extensively used by modern painters. With recent research highlighting the occurrence of various degradation phenomena in semiconductor paints, it is clear that their detection by conventional optical fluorescence imaging and microscopy is limited by the complexity of historical painting materials. Here, we illustrate and prove the capabilities of time-resolved photoluminescence (TRPL) microscopy, equipped with both spectral and lifetime sensitivity at timescales ranging from nanoseconds to hundreds of microseconds, for the analysis of cross-sections of paint layers made of luminescent semiconductor pigments. The method is sensitive to heterogeneities within micro-samples and provides valuable information for the interpretation of the nature of the emissions in samples. A case study is presented on micro samples from a painting by Henri Matisse and serves to demonstrate how TRPL can be used to identify the semiconductor pigments zinc white and cadmium yellow, and to inform future investigations of the degradation of a cadmium yellow paint.